SISTEM PENGENDALIAN INTERNAL KUALITAS AUDIT DAN TATA KELOLA PERUSAHAAN TERHADAP LABA PERUSAHAAN - Mizan, Mizan; Sunardi, Sunardi (Balance : Jurnal Akuntansi dan Bisnis, 2023)
This Research Aims To Know The Internal Control System Of Audit Quality And Corporate Governance For Manufacturing Company Profits In The Industrial Sector Listed On The Indonesia Stock Exchange For 2017-2021. The type of research used in this research is associative research. The research location is located at the Muhammadiyah University Palembang Investment Gallery. The Data Used Is Quantitative Data With Documentation And Bibliographical Data Collection Methods. The results of this study can be concluded that the internal control system for audit quality and corporate governance on corporate profits. If the internal control system, audit quality and corporate governance are strong, the company's profit will increase, if the internal control system, audit quality and corporate governance are strong, the company's profit will decrease.